‘Navigating a lonely road to adulthood with an ever-changing map’; a framework and case study protocol exploring the transition to adulthood, mental health literacy and occupational balance among Swedish young adults - Martin Karaba Bäckström; Sonya Girdler; Ulf Jonsson; Carita Håkansson; Annika Lexén (PLoS ONE, 2025)
Background Recent reports point to a global and Swedish national mental health crisis among young adults. It is widely recognised that this phase of ‘emerging adulthood’ involves many challenges, stressors and uncertainties that can negatively impact mental health and well-being. In addition, these strains may be exacerbated by rapid contemporary changes in technological, societal and sociocultural contexts. Developing and tailoring interventions bolstering the mental well-being of young adults requires deeper insights into their lived experiences, self-perceived strengths and challenges. Aim This paper has two interconnected purposes: Firstly, presenting relevant theories and theoretical perspectives at the individual, group and societal levels providing a rationale for theorised study propositions underpinning a situational analysis of Swedish young adults. Secondly, building on this theoretical foundation, the aim is to describe a protocol for a case study and situational analysis examining how Swedish young adults from Generation Z experience their transition to adulthood, its impacts on their mental health, describing their mental health literacy, occupational balance, and support needs. Method This case study protocol outlines a holistic, single-case study design employing a flexible approach. Data will be collected in Sweden through focus groups and individual interviews with stakeholders, young adults, and their parents. Existing and available mental health and well-being promotion in Sweden will be mapped through online searches. The various data sources will initially be analysed separately using thematic analysis. Subsequently the subthemes and themes will be jointly analysed across participant groups using pattern matching in workshop formats. Conclusions The results of this case-study are expected to generate new knowledge of the reasons underpinning the increase in mental ill-health among young adults in Sweden. This knowledge will subsequently inform the future co-production and core design features of a digital mental e-health intervention aimed at promoting mental well-being among Swedish young adults aged 18–29.